Differential Study of the Beliefs Concerning Home Care and Death among Relatives Caring for Patients with HIV/AIDS and cancer - Barbieri,André Luiz (2005)
Several forms of treatment have been developed regarding how AIDS and cancer are dealt with. Although these diseases have elicited prejudiced attitudes, the persons involved in patient care have permitted the advance of ideas and discussions towards the humanization of these diseases. The objective of the present study was to survey the beliefs of relatives of patients with HIV/AIDS and cancer regarding death and home care in an attempt to determine the characteristics of such beliefs. For this purpose we used Fishbein-Ajzen's affective-cognitive framework which conceives attitude as resulting from the association of beliefs and affects associated with a given phenomenon. Thirty-five relatives of patients with HIV/AIDS and 35 relatives of patients with cancer were studied. The attitudes of the relatives surveyed in this study revealed the lack of preparation and the difficulties of subjects in facing death and patient care. Although having pointed out that love and faith in God as important in family relations, day-to-day experiences of caregiving and of impending death, characteristics related to social exclusion and the vulnerability elicited by these diseases emerged.